ANALISIS PERILAKU IBU HAMIL DALAM MELAKUKAN PERAWATAN PAYUDARA DI KLINIK KHADIJAH LUPUK PAKAM - Reni Agustina Harahap, SST., M.Kes (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2017)
ABSTRACT Breast care is one important part that must be considered as preparation for breastfeeding later, and the breasts will be more enlarged and the nipple will be darker color and also more sensitive. The purpose of this study was to determine the behavior of pregnant women about breast care during pregnancy at Khadijah clinic Lubuk Pakam. The research design that will be used in this research is descriptive with cross sectional approach of univariant data analysis with total sampling method. This study uses a questionnaire instrument. From the results of the study is expected to further researchers more specific research variables are more varied or from the correlation, in order to see whether there is a relationship between the behavior of pregnant women in breast care to breast milk production. Keywords : Behavior of pregnant women, breast care